Some effects of low pH on chloride exchange in human red blood cells (The Rockefeller University Press, 1975)
In order to test the range of pH values over which the titratable carried model for inorganic anion exchange is valid, chloride self- exchange across human red blood cells was examined between pH 4.75 and 5.7 at 0 decrees c. It was found that chloride self-exchange flux had a minimum near pH 5 and increased again with further increase in hydrogen ion activity. The Arrhenius activation energy for chloride exchange was greatly reduced at low pH values. The chloride flux at pH 5.1 did not show the saturation kinetics reported at higher pH values but was proportional to the value of the chloride concentration squared. In addition, the extent of inhibition of chloride self-exchange flux by phloretin was reduced at low pH. Our interpretation of these findings is that the carrier-mediated flux becomes a progressively smaller fraction of the total flux at lower pH values and that a different transport mode requiring two chloride ions to form the permeant species and having a low specificity and temperature dependence becomes significant below pH5. A possible mechanism for this transport is that chloride crosses red cell membranes as dimers of HCl at these very low pH values.